2020
DOI: 10.1002/ceat.201800546
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Characteristics of High‐Viscosity Fluids under Forced Vertical Vibration

Abstract: The mixing characteristics of two initially stratified high‐viscosity fluids with a free surface under forced vertical vibration were studied experimentally and numerically. The flow characteristics and dynamics of the free surface and interface between liquids were analyzed and the effects of the vibration parameters on the mixing process were evaluated. The degree of mixing was determined by the frequency and amplitude of vibration. Effective mixing could not be achieved by merely using the deformation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…It can be observed that, with an increase in the grid density, the variation in the wind speed remains below 5%. This confirms that the meshing scheme satisfies the grid independence criterion [23]. The grid cell dimensions for three groups are detailed in Table 2.…”
Section: Computational Fluid Dynamics (Cfd) Simulationsupporting
confidence: 69%
“…It can be observed that, with an increase in the grid density, the variation in the wind speed remains below 5%. This confirms that the meshing scheme satisfies the grid independence criterion [23]. The grid cell dimensions for three groups are detailed in Table 2.…”
Section: Computational Fluid Dynamics (Cfd) Simulationsupporting
confidence: 69%
“…To achieve the effect of vibration mixing in the special case of grid motion, the slip grid technique can be used. 27 In this paper, a slip-grid model is implemented to apply the vibration, such that the wall motion of the container becomes a function of the velocity described in (2). This model is able to describe a moving mesh scenario where the mesh nodes make rigid motions within a specific region of the moving mesh.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve the effect of vibration mixing in the special case of grid motion, the slip grid technique can be used. 27 In this article, a slip-grid model is implemented to introduce the vibration, making the vessel's wall motion a function of the velocity described in Equation ( 2). The conservation equation in integral form for a generic scalar on a control body V with boundary motion and a moving grid can be written as:…”
Section: Control Equations and Boundary Conditionsmentioning
confidence: 99%
“…To achieve the effect of vibration mixing in the special case of grid motion, the slip grid technique can be used 27 . In this article, a slip‐grid model is implemented to introduce the vibration, making the vessel's wall motion a function of the velocity described in Equation (2).…”
Section: Experimental Setup and Simulation Modelmentioning
confidence: 99%